The Influence Of Training, Competence, And Leadership On Lecturer Career Development Through Work Motivation As An Intervening Variable - Reza Jordan; Gurawan Dayona Ismail; Nunung Ayu Sofiati; Mochammad Mukti Ali; Yoyo Sudaryo (Green Publisher Indonesia, 2025)
The results of the study indicate that training has an effect on work motivation. The original sample value for variable X1 (training) on Y (work motivation) is 1.14, with a t-statistic of 13.524 and p-values of 0.000, which is smaller than the significance level, indicating a positive and significant influence between variable X1 (training) and Y (work motivation). The original sample value implies that better and higher training leads to better and higher work motivation. Furthermore, competence influences work motivation. The original sample value for variable X2 (competence) on Y (work motivation) is -0.177, with a t-statistic of 2.593 and p-values of 0.01, which is smaller than the significance level, indicating a non-positive but significant influence of variable X2 (competence) on Y (work motivation). Leadership influences work motivation. The original sample value for variable X3 (leadership) on Y (work motivation) is 0.03, with a t-statistic of 0.771 and p-values of 0.441, which is smaller than the significance level, indicating a positive and significant influence of variable X3 (leadership) on Y (work motivation). The original sample value implies that better and higher leadership leads to better and higher work motivation. Subsequently, work motivation influences career development. The original sample value for variable Y (work motivation) on Z (career development) is 0.348, with a t-statistic of 1.645 and p-values of 0.1, which is smaller than the significance level, indicating a positive and significant influence of variable Y (work motivation) on Z (career development).